Hipertensi pada Anak di RS dr. Sardjito Yogyakarta - A.K. Pungky, M.P. Damenik (Fakultas Kedokteran Universitas Gadjah Mada, 2006)
Background: The prevalence of hypertension cases in children which were categorized into primary and secondary hypertension was 1-3%. The most common and severe cases were caused by renal diseases. Symptomatic examinations were performed to identity the factors related to hypertension.Objective: To know the clinical appearance of hypertension in children, the infection, and its complications. Patelnts &Methods: A retrospective analysis on children with hypertension hospitalized at Dr. Sardjito Hospital from 1996-2005 was conducted. The criteria of hypertension were based on 'The Second Task Force on Blood Pressure Control in Children